Politik Hukum Islam dalam Pengaturan Tentang Kesusilaan di Indonesia (Studi UU Nomor 44 Tahun 2008 Tentang Pornografi) - Ismail Marzuki (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
This article tries to explore how the influence of Islamic law politics in drafting Law No. 44 of 2008 on Pornography. A qualitative approach was employed in this study. The treatise of Indonesia’s Pornography Law was collected as the primary data. The findings expose that there was the effect of Islamic law politics in drafting Law No. 44 of 2008 on Pornography. It can be noticed from the active involvement of Islamic political parties in parliament and the House of Representatives (DPR) members from the nationalist parties possessing an Islamic background in promoting the law enactment. Likewise, the Indonesian Ulema Council (MUI) and Islamic mass organizations also actively encouraged the issuance of this law. Another result highlights that there was a strong debate between political fractions in the DPR, including the Gerindra Party (PG), the United Development Party (PPP), the Democratic Party (PD), the National Mandate Party (PAN), the National Awakening Party (PKB), the Democratic Vanguard Star (BPD), the Star Reform Party (PBR), the Prosperous Justice Party (PKS), and the mass organizations that proposed the ratification of the Pornography Law draft, and other fractions, namely: the Indonesian Democratic Party of Struggle (PDIP), the Prosperous Peace Party (PDS), and the mass organizations that supported the refusal of the law draft ratification.